THE EFFECTIVENESS OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TO IMPROVE WRITING IN DESCRIPTIVE TEXTS - Ibriza, Kamila Nurul (ELT Forum: Journal of English Language Teaching, 2017)
This paper is based on a study which investigated the eighth grade students’ achievement in writing descriptive text. The study aimed to find out the effectiveness of Cooperative Integrated Reading and Composition (CIRC) technique to teach writing of descriptive and to investigate the significant difference of students’ writing achievement between the students who were taught using that technique and those who were not. The study employed quasi-experimental non-equivalent control group design. The data were pre-test, and post-test scores. The result of the study shows that the mean score of the pre-test in the experimental group is 63.97, while in the control group is 64.46. Therefore, the result of post-test increased. In the post-test, the mean score of the experimental group is 76.26, and the control group gets 71.13. Moreover, the t-test result is 2.847 and ttable is 2.024. It can be clearly seen that tvalue is higher than ttable. It means that the hypothesis of H1 is accepted and H0 is rejected. Based on the proven hypothesis, it could be proven that Cooperative Integrated Reading and Composition (CIRC) is effective to teach writing of descriptive text for the eighth grade students of junior high school students.